Flipped classroom applied to Neurosurgery in undergraduate medical education - R Gutiérrez-González; A Zamarron; A Royuela; G Rodriguez-Boto (BMC Medical Education, 2023)
Abstract Purpose To compare the academic achievement obtained in Neurosurgery in a class of undergraduate students according to the pedagogical methodology employed: flipped classroom (FC) versus traditional lecture. Students’ satisfaction with the FC model is also analyzed. Methods A quasi-experimental study was designed. The traditional lecture was the pedagogical method employed in teaching units (TUs) 1, 2, and 3 (61, 60, and 66 enrolled students, respectively), whereas TU 4 (69 enrolled students) used the FC methodology. Results The dropout rate was lower, whereas the academic achievement and the rate of correct answers were higher in TU 4 compared to the rest of the TUs, but these results were not statistically significant. However, the mean score obtained in Neurosurgery was significantly higher in TU 4 compared to the rest of the TUs (p = 0.042). Active learning activities based on clinical cases were positively emphasized. The main weakness was with the time consumed for video-recorded lecture viewing. Conclusions The FC approach showed better academic results than traditional lectures when comparing students in the same Medical School during the same academic year undergoing the same exam. The students rated the FC approach positively, considering it stimulating and useful for learning.